Indeks Kesesuaian Wisata Di Pantai Dolok Oan, Cristo Rei, Dili, Timor Leste - Jenisia Barros Soares; I Gusti Ngurah Putra Dirgayusa; Ni Luh Putu Ria Puspitha (Journal of Marine and Aquatic Sciences, 2022)
East Timor is a country located in the northern continent with an area of 14.874 km². East Timor has a lot of natural resources, one of which is the beach located in Est Timor in the capital city of Dili, located in Cristo Rei area Dolok Oan beach. Dolok Oan beach is a white sand beach that has the sand characteristics, sea water so it is suitable for recreation but has not utilized optimally. Therefore the purpose of this study is to determine the suitability index of tourism on the beach and to identify the limiting factors of the suitability index of tourism in the Dolok Oan coast region. A tourism suitability index (TSI) study was carried out at Dolok Oan beach, Cristo Rei, Dili, Timor - Leste, in January 2019. Pusposive sampling is used as a method for data collection. The dat collected are included: coastal type, beach width, water depth, coastal slope, water base material, water flow, velocity, waters brightness, coastal clousure, harmful biota, and freshwater availability. The analysis of IKW for recreation beach category refers to the matrix of tourism and tourism conformity classification. The limiting factor of IKW in Dolok Oan Beach is coastal land cover and wide beach. IKW value for tourism activities in the beach recreation category at Dolok Oan Beach value of 93,58% are category as suitable (S1). At Dolok Oan beach